Design of an Ultra-Wideband Power Divider with Good In-Band Performance and Sharp Roll-Off Skirt. Issue 1 (2nd January 2016) - Xu, Xin; Tang, Xiaohong
ABSTRACT: In this article, a novel ultra-wideband power divider is presented. To achieve ultra-wideband performance and a sharp roll-off skirt, the parallel coupled lines and a short-circuited line are introduced on each side of the coupled three-line microstrip structure. Through even- and odd-mode analysis, the analytical design equations for this proposed power divider are obtained. A prototype power divider is designed and fabricated to demonstrate the performance of the proposed power divider. The simulated and measured results show that the proposed power divider has achieved the predicted features within the specified 3.1–10.6-GHz ultra-wideband range.